The Relationship Between Crime-Related Television Viewing and Perceptions of the Death Penalty: Results of a Large Cross-Sectional Survey Study - Till, Benedikt; Arendt, Florian; Niederkrotenthaler, Thomas (Frontiers in Psychology, 2021)
Background: According to cultivation theory, distorted representations of social reality on television can lead to distorted perceptions of reality among viewers. For example, the death penalty has been abolished in most Western countries a long time ago, but is often portrayed or mentioned in US crime shows, which are very popular outside the United States. Previous research suggests that the amount of television viewing can be associated with erroneous perceptions of the use of the death penalty—even when the death penalty is not used in the respective country. Unfortunately, available evidence on this association is inconclusive. Methods: In a cross-sectional web-based survey, we used quota-based sampling techniques to recruit 1,002 individuals representative of the Austrian population in terms of gender, age, education, and region of residence. We asked about their weekly amount of television viewing and use of US crime dramas and measured their beliefs on the use of the death penalty in Austria. Results: Although television viewing in general was not associated with erroneous perceptions of the death penalty (i.e., no overall across-the-board cultivation effect), data analysis provided supporting evidence for the idea of a genre-specific cultivation effect: The more US crime shows participants watched, the more likely they were to mistakenly believe that the death penalty is used in Austria. This association held true even after controlling for the gender, age, and education of participants. Conclusion: The finding that watching US crime shows, which are based on social reality in the United States, is associated with Austrian viewers' confusion with regards to perceptions of the death penalty is consistent with the genre-specific cultivation hypothesis. Some viewers may be guided more by mediated reality than by actual social reality.